Leading Ecuadorian companies in the wine tourism sector and their positioning on the social medium facebook - Toledo Macas, R. (2016)
In recent years wine tourism has contributed to the positive evolution of tourist destinations, providing opportunities for development for local economies through the generation of employment and its multiplying effects on other transversal sectors. Oenology gives tourists the chance to discover more about local culture and enjoy sensorial experiences and sensations whilst indulging in the pleasure of tasting a regions traditional wines. In this sense, and in the specific case of Ecuador, the presence of prestigious wine-making companies with an excellent national and international reputation contribute to boosting wine tourism. Mention must be made of two of the countrys leading wine producers: Dos Hemisferios, situated in the province of Guayas, in the region of Playas, and the Chaupi Estancia Winery, in the province of Pichincha, in Yaruquí. This study aims to identify the positioning of these companies, as representatives of Ecuadors wine industry, on the social medium Facebook. The conclusions point to the need to take advantage of the opportunities social media offer today as a communication channel, in order to improve the position of wine tourism in Ecuador. © Springer International Publishing Switzerland 2016.